Incidence of Acute Mitral Regurgitation in Patients with Severe Mitral Stenosis after Post Percutaneous Transvenous Mitral Commissurotomy - Fouzia Goher, Muhammad Irfan, Anwaar Ul Hassan, Marryam Rauf, Khursheed Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the incidence of Acute Mitral Regurgitation in severe mitral stenosis patients done with Post Percutaneous Transvenous Mitral Commissurotomy (PTMC). Methodology: This cross-sectional study was held in the Bahawalpur Heart Center, Bahawalpur for the duration of six months from March 2022 to September 2022. The study included 80 patients, regardless of gender, between the ages of 19-80 years and who had not undergone PTMC. Those with mitral regurgitation and mitral stenosis, left atrial clots, and patients with end- stage renal disease were not included in the study. The predefined Proforma was used as a research tool to document the medical records of PTMC patients. The patient's name, age, echo results, sex, course of treatment, complications and post- procedure information are among the variables documented on the proforma. Results: The patients mean age recorded in this study was 43.18 ± 10.33. The maximum of the PTMC patients, were females 65(80%). The majority of PTMC patients were found to have "Trace" MR, which is a very slight leak in a heart valve. Before the procedure, there were 30 (37.5%) patients with trace MR, followed by 27 (33.8%) patients with mild MR. Before the procedure, 8 (10%) patients had no MR-related difficulties, 5 (6.2%) had moderate MR, and 4 (5%) had mild-moderate MR. After the procedure, 63 (78.8%) of the patients experienced "no complications," 12 (15%) of the PTMC patients experienced "severe mitral regurgitation," 4 (5%) experienced a local hematoma, and cardiac tamponade was seen in one patient. Post-procedure, one patient died. Post-stratification research revealed that 61.3% of patients without a prior history of commissurotomy and the majority of female patients had no complications. While 22.4% of those who never had a prior commissurotomy experienced severe MR overall Conclusion: Our research showed that only a small proportion of PTMC patients had severe mitral regurgitation. Overall, the treatment was successful and safe. Keywords: Cardiac Tamponade, Local Site Complications, Post Percutaneous Transvenous Mitral Commissurotomy, PTMC, Mitral Regurgitation, MR